Implementasi Algoritma Particle Swarm Optimization (PSO) untuk Optimasi Pemenuhan Kebutuhan Gizi Balita - Leni Istikomah; Imam Cholissodin; Marji Marji (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2017)
Toddlers are children with 1-5 years age range. According to Riskesdas, in the year 2007, 2010, and 2013 the percentage of cases of malnutrition tends to increase, especially in toddlers. In the fulfillment of nutrients, one type of food alone is not enough so it requires a variety of food ingredients that contain all the elements of nutrients. Efforts to improve child nutrition have been done by the government through Posyandu to monitor and provide more servants to toddlers. Nutrition needs of Indonesian people has been set in the guidelines of Pedoman Gizi Seimbang by the Ministry of Health Republic Indonesia, including nutritional guidelines to meet the nutritional needs of infants. However, the nutritional guidelines only provide the value of the nutrient content of each foodstuff, making it difficult for Posyandu staff to provide menu variations to fit the needs of children according to their health condition. In this research give recommendation of variation of foodstuff automatically by using optimization process of Particle Swarm Optimization algorithm so that it can facilitate Posyandu and parents of toddlers in providing daily food according to the nutritional needs of toddlers. Based on the test results, the most optimal parameter is the number of particles = 30, Wmin = 0.4, Wmax = 0.7, C1 = 2, C2 = 1.5, Number of iterations = 40 and Upper Limit Permutation number of 75 resulting in average energy, protein, fat and carbohydrate difference of 16.04%, -8.08%, 2.85% and 25.98% which can save parents toddlers by 28.56%.